Quality nursing work life among nurses in Hail Region, Kingdom of Saudi Arabia: Redefining the boundaries of work and life - Albaqawi, Hamdan Mohammad (Advances in Social Sciences Research Journal, 2018)
Defining the boundaries of work and life can increase the contentment and satisfaction of the workers. This research employed a quantitative cross-sectional design to investigate the quality nursing work life amongst nurses. The respondents include the staff nurses from the Ministry of Health hospitals of Hail City, Kingdom of Saudi Arabia. The instrument used was adapted from Turkish version of quality of nursing work life scale as it is relevant to the local context of Hail Region. The instrument was subjected to reliability test resulted to high reliability of .93. Ethical considerations were fully ensured throughout the research process. Generally, the quality nursing work life as regards work environment revealed 3.72+0.97; relation with managers resulted to 3.78+1.06; work conditions revealed 3.23+1.18 on job perception revealed 3.92+0.83 and 3.83+0.91 on support services. Further result shows pronounce significant differences on the age of the nurses and work condition (p=0.011); Civil status and support services (p=0.012); and education to relation with managers (p=0.000). Specific variables can greatly influence the quality nursing work life of staff nurses in the hospitals of Hail Region, Kingdom of Saudi Arabia. The pronounce significant difference between the demographic variables such as age, civil status, and education suggest that staff nurses in the hospitals of Hail Region, Kingdom of Saudi Arabia needs to go beyond the expected standard. These specific variables can be of importance in making programs to improve the quality nursing work life.